Case report: Conversion therapy for advanced intrahepatic cholangiocarcinoma using PD-1 inhibitor plus S-1 and nab-paclitaxel - Li, Xiaocheng; Jiang, Zhiyang; Wu, Yongjuan; Gong, Wei; Liao, Xiaofeng; Li, Xiaogang (Frontiers in Oncology, 2022)
Intrahepatic cholangiocarcinoma (iCCA) is a highly malignant hepatobiliary tumor with a high rate of advanced disease at initial presentation. Conversion into resectable iCCA is important for improving the prognosis. Immunotherapy-based regimens are being increasingly used for treating advanced iCCA in recent years. However, the use of combined chemotherapy and immunotherapy for conversion has rarely been reported. The aim of this report was to present the outcomes of a 52-year-old female patient with IIIB iCCA. The patient was treated with a programmed cell death protein-1 inhibitor plus S-1 and nab-paclitaxel. The postoperative histopathological results indicated pathologic complete response after six cycles of systematic treatment. The patient is currently disease-free for one year.